Yield gains in extra-early maize cultivars of three breeding eras under multiple environments - Badu-Apraku, Baffour; Yallou, C.G.; Obeng-Antwi, K.; Alidu, H.; Talabi, A.O.; Annor, B.; Oyekunle, M.; Akaogu, I.C.; Aderounmu, M. (Wiley, 2017)
Availability of extra-early maize cultivars has facilitated the expansion of maize production into savannas of West and Central Africa (WCA). Fifty-six extra-early maize cultivars of three breeding eras;1995 to 2000, 2001 to 2006, and 2007 to 2012 were evaluated for 2 yr under 24 multiple-stress and 28 non-stress environments in WCA. Objectives of the study were to determine genetic improvement in grain yield of cultivars developed during the breeding eras, and identify high-yielding and s multiple-stress and non-stress environments. Yield gains from era 1 to era 3 under multiple stresses was associated with increased days to anthesis, reduced stalk lodging, and improved husk cover. Cultivars 2004 TZEE-Y Pop STR C4, TZEE-W Pop STR QPM C0, and TZEE-W Pop STR BC2 C0 of era 2; and TZEE-W STR 107 BC1, TZEE-W Pop STR C5, and 2012 TZEE-Y DT STR C5 of era 3 were high-yielding and stable across multiple-stress environments while 98 Syn EE-W from era 1, FERKE TZEE-W STR, TZEE-W Pop STR C3, and TZEE-Y Pop STR QPM C0 from era 2, and TZEE-W Pop STR C5, 2009 TZEE-OR2 STR QPM, 2009 TZEE-W STR, TZEE-Y STR 106, and TZEE-W DT C0 STR C5 from era 3 were outstanding across non-stress environments and should be tested extensively and commercialized. Considerable improvement has been made in breeding for multiple-stress tolerant extra-early maize cultivars.